FORMULASI DAN UJI STABILITAS LOTION SARI BUAH TOMAT (licopersicon esculentum mill) KOMBINASI KUNYIT (Curcuma domestica Vall) SEBAGAI PELEMBAB KULIT - Nina Irmayanti Harahap (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2021)
Antioxidants is contained in various types of fruit and vegetables included of juice tomatoes (Lycopersicum esculentum Mill)that have nutritional value and benefits for the body like lycopene, and vitamin C as antioxidants. Lycopene is function as a strong antioxidant to control free radical. Tumeric (Curcuma domestica Vall) is known have enough curcumin and strong antioxydants content too, and so it has some pharmacological effects. Tomatoes and Tumeric extract (EKSBT) can be made as pharmaceutical preparations in hand and body lotion (H&B lotion),because antioxidants are important components that are used for body protection from ultra violet light and can be applied in the form of a lotion. The purpose of this study was to saw the stability of the H&B lotion combination of that Variations.Combination tomatoes and turmeric extract formulated with concentrations lotion are of 5%, 10%, and 15%. The lotion of EKSBT these combination were evaluated some test there are organoleptic, homogeneity, pH test, spreadability, irritation and preference test.EKSBT combination can be formulated into lotion preparations. The various of all concentrations lotion EKSBT showed that stable during instorage, give a homogeneous yellow color with pH of 5-6 and a spread of 5-6 cm, does not irritate the skin and is preferably the volunteer.Physical stability EKSBT lotion test all concentration are stable, the preferred test of odor, easy to be smeared and moisturizing shows that the most preferred EKSBT lotion is the highest concentration 15%.